The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1080/15332640.2017.1292418
|View full text |Cite
|
Sign up to set email alerts
|

Perceived discrimination among racial and ethnic minority drug users and the association with health care utilization

Abstract: People who use drugs (PWUDs) are at increased risk for several medical conditions, yet they delay seeking medical care and utilize emergency rooms (ERs) as their primary source of care. Limited research regarding perceived discrimination and PWUDs’ use of health care services exists. This study explores the association between interpersonal and institutional racial/ethnic and drug use discrimination in health care settings and health care utilization among respondents (N =192) recruited from Methadone Maintena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 47 publications
1
24
0
3
Order By: Relevance
“…Access to good quality healthcare should be a basic human right for any person, irrespective of whether they use drugs. In other settings, a lack of engagement in health services can stem from stigma and discrimination experienced from past encounters with the health system [103][104][105][106][107][108][109][110]. In one study from Thailand, 26% of PWID reported avoiding health services, with factors associated with avoidance of healthcare including experience of verbal abuse, having been refused medical care, and having experienced previous barriers to accessing health care [105].…”
Section: Restrictive Drug Policies and Criminalization Of Drug Usementioning
confidence: 99%
“…Access to good quality healthcare should be a basic human right for any person, irrespective of whether they use drugs. In other settings, a lack of engagement in health services can stem from stigma and discrimination experienced from past encounters with the health system [103][104][105][106][107][108][109][110]. In one study from Thailand, 26% of PWID reported avoiding health services, with factors associated with avoidance of healthcare including experience of verbal abuse, having been refused medical care, and having experienced previous barriers to accessing health care [105].…”
Section: Restrictive Drug Policies and Criminalization Of Drug Usementioning
confidence: 99%
“…Nesse sentido, o preconceito e o estigma são processos sociais similares que podem resultar em discriminação, estereótipos e rejeição social. Isso se deve ao fato de os transtornos mentais serem entreme-ados por estereótipos, mas são as pessoas envolvidas com a dependência de drogas que mais sofrem com tais processos (1,5,(11)(12)(13)(14) .…”
Section: Discussionunclassified
“…Tais questões culminam no estado pleno das desigualdades, denominado exclusão social. Caracterizado pelo processo acumulativo e multidimensional que separa e inferioriza as pessoas, os grupos, as comunidades e os territórios (4,12,15) . A exclusão social coexiste em vários tipos de fenômenos sociais, tais como o desemprego, a marginalidade, o preconceito e o pauperismo (17)(18) .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…13 This may be attributed to generally less health care access in rural areas, 14 less access to SSPs due to distance or limited hours, 13 and greater fear of stigma in health care settings. 15 SSPs may serve to fill this gap by providing more culturally sensitive, stigma-free health services and connecting PWID to appropriate care.…”
mentioning
confidence: 99%